2021
DOI: 10.1002/jsfa.11626
|View full text |Cite
|
Sign up to set email alerts
|

Effects of exogenous sucrose and selenium on plant growth, quality, and sugar metabolism of pea sprouts

Abstract: BACKGROUND Pea sprouts are considered a healthy food. Sucrose is a key nutritional factor affecting taste and flavor. Meanwhile, selenium (Se) is an essential micronutrient that plays multiple roles in wide variety of physiological processes and improves crop quality and nutritional value. Nonetheless, the effects of the combination of sucrose and Se treatment on growth, quality, and sugar metabolism of pea sprouts have not been explored. RESULTS The results revealed that sucrose at 10 mg L−1 obviously increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 26 publications
3
17
0
Order By: Relevance
“…Mainly because leaf proteins are degraded and N is transported and stored in the perennial, woody organs of the tree(Tagliavini et al, 1997). The soluble sugar and fructose contents were increased and sucrose contents was decreased with the Se doses increased, the glucose content was increased by Se without Se dose in uence(Tan et al, 2021). Our study showed the leaf sorbitol, fructose, and maltose were increased with the Se doses increase and the signi cant positive linear between the three sugar and Se content.…”
mentioning
confidence: 51%
“…Mainly because leaf proteins are degraded and N is transported and stored in the perennial, woody organs of the tree(Tagliavini et al, 1997). The soluble sugar and fructose contents were increased and sucrose contents was decreased with the Se doses increased, the glucose content was increased by Se without Se dose in uence(Tan et al, 2021). Our study showed the leaf sorbitol, fructose, and maltose were increased with the Se doses increase and the signi cant positive linear between the three sugar and Se content.…”
mentioning
confidence: 51%
“…Exogenous Suc is known to affect sugar metabolism [ 58 ]. The results of a previous study revealed that 10 mg/L exogenous Suc increased levels of soluble proteins, soluble sugar, fructose, glucose, and Suc in pea sprouts [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…Vc content was determined by molybdenum blue colorimetric method ( Tan et al, 2021 ). Briefly, fresh leaf and flower stalk samples (1.0 g) were extracted using 25 mL of oxalic acid EDTA solution, and then one mL of supernatant was mixed with 0.5 mL of phosphate-acetic acid, two mL of 5% ammonium molybdate.…”
Section: Methodsmentioning
confidence: 99%